Status of the Vertebrate Fauna in Selected Sites of Pagatban River, Negros Oriental, Philippines - Bucol, Abner A.; Carumbana, Esther E.; Averia, Leonardo T. (Silliman Journal, 2022)
An assessment on the status of the vertebrate fauna of Pagatban River in southwestern Negros Island was conducted from February to April and August to November 2010 using purposive sampling techniques. There were 82 species of birds, eight species of amphibians, 14 species of reptiles, and nine species of mammals observed. Data on the population estimates of the Endangered Limestone Frog Platymantis spelaeus is also presented. The Philippine Crocodile Crocodylus mindorensis is probably extinct in the area